A novel biologically active acid stable liposomal formulation of docosahexaenoic acid in human breast cancer cell lines. (25th May 2016) - Skibinski, Christine G.; Das, Arunangshu; Chen, Kun-Ming; Liao, Jason; Manni, Andrea; Kester, Mark; El-Bayoumy, Karam
Abstract: Purpose: The risk of breast cancer can be influenced by certain dietary components, such as the amount and type of dietary fatty acids ingested. Docosahexaenoic acid (DHA), a component of fish oil, is known to suppress rat mammary carcinogenesis, reduce cell growth and induce apoptosis in human breast cancer cell lines. The purpose of this study was to develop a novel nanoliposomal formulation that would encapsulate a concentrated amount of DHA and utilize lipids that could protect DHA from pH fluctuations and oxidation. Methods: We developed an acid stable liposome formulation of DHA by utilizing ether and phytanyl lipids similar in structure to those found in Archaea, known to endure high acidity and temperature; we compared its biological activities with free DHA in human breast cancer cells. Results: The mean size of the liposomal DHA was 137 ± 12 nm with a slightly negative charge; the encapsulation efficiency of DHA in the liposomes as determined by LC-MS/MS ranged from 60 to 80%; our formulation is resistant to oxidation and stable over a range of pH (1.0–7.4) at 37 °C for a duration of two hours. In MCF-7 cells, liposomal DHA (IC50 38.8 μM) significantly reduced cell viability more effectively than free DHA (IC50 72.5 μM, p = 0.0017). In MDA-MB-231 cells, liposomal DHA was also marginally more effective. Liposomal DHA was more effective than free DHA in inducing apoptosis in both cell lines. It altered proteins involved in cell growth, cell cycle, and apoptosis more effectively than free DHA in both cell lines; it up-regulated p21 and cleaved PARP, while P-AKT and P-S6 were down-regulated. Conclusions: We developed a novel biologically active acid stable liposomal DHA as a potentially useful formulation for breast cancer prevention. Highlights: Developed a novel acid stable liposomal DHA (LDA). LDA formulation protected DHA from oxidation and pH fluctuations. LDA reduced proliferation and induced apoptosis more than DHA in cancer cells. LDA altered some proteins in a manner consistent with its antitumorigenic effects.